Charter schools: A U.S. case study and implications for Brazil - Paula Louzano; Lara Simielli (Education Policy Analysis Archives, 2020)
This article analyzes the case of school choice in the United States and its implications for the Brazilian context. This discussion is important to Brazil, given the fact that key actors are starting to advocate in favor of introducing charter schools and vouchers in the country. Evidence from countries that introduced this model can help shed some light on this debate. In this article, we will analyze the overall performance of school choice in the United States, especially charter schools, focusing on its implications on educational equity. The Brazilian educational system is highly unequal. Thus, if charter schools are not helping to enhance the overall quality and equity in the United States, it may not be a policy to be pursued in Brazil. In this scenario, focusing on the idea that school choice is the answer may divert the attention from systemic policies that can contribute to improve education such as high-quality early childhood education, increased education funding, after-school programs, and teacher professional development.